Adaptation and validation of the Barnes-Jewish Hospital-Stroke Dysphagia Screen for the portuguese version/ Adaptação e validação do Barnes-Jewish Hospital-Stroke Dysphagia Screen para versão portuguesa/ Adaptación y validación del Barnes-Jewish Hospital-Stroke Dysphagia Screen para la versión portuguesa - Oliveira, Isabel de Jesus (2021)
Objective: adapt and validate the Barnes-Jewish Hospital-Stroke Dysphagia Screen (BJH-SDS) instrument to European Portuguese speakers. Method: BJH-SDS underwent a rigorous process of cross-cultural adaptation and was validated with acute stroke patients in five stroke units from February 2018 to April 2019. For data analysis, SPSS 25 was used. Nurses performed the screening on admission, and inter-rater reliability was established. Results of clinical bedside evaluation were compared with those provided by BJH-SDS. Results: cross-cultural adaptation was performed and completed successfully without difficulties. For validation, 226 acute stroke patients were enrolled. The incidence of dysphagia using BJH-SDS was 72.1%, and a highly significant relationship (χ2 = 87.81; p <0.001) was observed compared to clinical bedside evaluation, with an area under the ROC curve of 0,765. Excellent inter-rater reliability (k=0.977) was reached. Conclusion: results suggest that the Portuguese version of the BJH-SDS is a reliable dysphagia screening test. It is straightforward to be administered bedside by nurses with minimal training required. It was also shown to have adequate sensitivity to assist in decision-making to refer stroke patients for a more comprehensive evaluation.